2015
DOI: 10.1128/iai.02611-14
|View full text |Cite
|
Sign up to set email alerts
|

Host Hydrogen Rather than That Produced by the Pathogen Is Important for Salmonella enterica Serovar Typhimurium Virulence

Abstract: Salmonella enterica serovar Typhimurium utilizes molecular hydrogen as a substrate in various respiratory pathways, via H 2 -uptake enzymes termed Hya, Hyb, and Hyd. A different hydrogenase, the hydrogen-evolving Hyc enzyme, removes excess reductant during fermentative growth. Virulence phenotypes conferred by mutations in hyc genes, either alone or in combination with mutations in the H 2 -uptake enzyme genes, are addressed. Anaerobically grown ⌬hycB or ⌬hycC single-deletion strains were more sensitive to aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 38 publications
3
25
0
Order By: Relevance
“…g . mutants devoid of H 2 -uptake hydrogenase activity are viable under laboratory conditions 34 , 40 , 41 , 46 . It seems this is not the case for C .…”
Section: Discussionmentioning
confidence: 99%
“…g . mutants devoid of H 2 -uptake hydrogenase activity are viable under laboratory conditions 34 , 40 , 41 , 46 . It seems this is not the case for C .…”
Section: Discussionmentioning
confidence: 99%
“…The respiration of H 2 is important during the infection process followed by Salmonella enterica serovar Typhimurium . The S. enterica genome encodes four [NiFe]‐hydrogenases, termed Hyd‐1, Hyd‐2, Hyd‐3, and Hyd‐5.…”
mentioning
confidence: 99%
“…The S. enterica Hyd‐5 isoenzyme shares structural similarities with Hyd‐1, but is synthesized under aerobic conditions and mouse model studies have shown that S . enterica Hyd‐5 is expressed during infection .…”
mentioning
confidence: 99%
“…Typhimurium, can remove excess reductant generated during acid stress by producing H 2 and consuming protons, so the expression of hydrogenase is likely involved in the pH response and regulation (Zbell and Maier, 2009 ; Noguchi et al, 2010 ). HycA is thought to regulate the Hyc operon, HycD is a transmembrane protein, HycE is the Ni-containing large subunit of Hyc-hydrogenase, and HycI is known to play an important role in the maturation of the formate hydrogenlyase (FHL) complex (Lamichhane-Khadka et al, 2015 ). In the present study, the HycADEHI genes were up-regulated in aTF, with log2 fold changes of 2.1 to 3.7, and all of these genes are associated with hydrogenase.…”
Section: Discussionmentioning
confidence: 99%